The metabolic phenotype of patients with primary aldosteronism: impact of subtype and sex – a multicenter-study of 3566 Caucasian and Asian subjects. Issue 3 (21st July 2022) - Spyroglou, Ariadni; Handgriff, Laura; Müller, Lisa; Schwarzlmüller, Paul; Parasiliti-Caprino, Mirko; Fuss, Carmina Teresa; Remde, Hana; Hirsch, Anna; O'Toole, Samuel Matthew; Thuzar, Moe; Petramala, Luigi; Letizia, Claudio; et al.
Abstract: Background: Accumulating evidence suggests that primary aldosteronism (PA) is associated with several features of the metabolic syndrome, in particular with obesity, type 2 diabetes mellitus, and dyslipidemia. Whether these manifestations are primarily linked to aldosterone-producing adenoma (APA) or bilateral idiopathic hyperaldosteronism (IHA) remains unclear. The aim of the present study was to investigate differences in metabolic parameters between APA and IHA patients and to assess the impact of treatment on these clinical characteristics. Methods: We conducted a retrospective multicenter study including 3566 patients with APA or IHA of Caucasian and Asian origin. We compared the prevalence of metabolic disorders between APA and IHA patients at the time of diagnosis and 1-year post-intervention, with special references to sex differences. Furthermore, correlations between metabolic parameters and plasma aldosterone, renin, or plasma cortisol levels after 1 mg dexamethasone (DST) were performed. Results: As expected, APA patients were characterized by higher plasma aldosterone and lower serum potassium levels. Only female IHA patients demonstrated significantly worse metabolic parameters than age-matched female APA patients, which were associated with lower cortisol levels upon DST. One-year post-intervention, female adrenalectomized patients showed deterioration of their lipid profile, when compared to patients treated with mineralocorticoid receptor antagonists. Plasma aldosterone levels negatively correlated with the BMI only in APA patients. Conclusions: Metabolic alterations appear more prominent in women with IHA. Although IHA patients have worse metabolic profiles, a correlation with cortisol autonomy is documented only in APAs, suggesting an uncoupling of cortisol action from metabolic traits in IHA patients.